Effect of personal characteristics on the rate of using a sick leave: field study on female employees of the general directorate of education in Jeddah - Alharthi, Wejdan Soud; Alhonaity, Mohammed Faleh (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed to identify the effect of personal characteristics on the rate of use of sick leave among the employees of the Department of Education in Jeddah. The descriptive approach was used and a questionnaire was prepared to collect field data from the sample of the study which included 260 employees. The data were analyzed using the SPSS. The study reached a number of results, the most important of which are: The average age was 4.50- the average was 4.13- the average extinction was 3.80 in the sample. The study also found that there were statistically significant differences at (α≤0.05) according to the age variable in the two dimensions of conscience and goodness. According to the age of the sample There is also a statistically significant difference between the educational levels of the sample members in the postpartum dimension at the level of statistical significance (α≤0.05), which means that the answer to the axes of the study instrument is affected by educational levels from level to level. In the light of the results, a number of recommendations were made to give attention to issues related to the work of working women and to increase their average utilization for sick leave, to raise awareness of the risks of sick leave and their impact on the performance and productivity of the Department.